Dimensionality of the Mental Toughness Questionnaire (MTQ48) - Perry, John L.; Strycharczyk, Doug; Dagnall, Neil; Denovan, Andrew; Papageorgiou, Kostas A.; Clough, Peter J. (Frontiers in Psychology, 2021)
Currently there is debate as to whether mental toughness is a unidimensional or multidimensional construct. To investigate the dimensionality of the Mental Toughness Questionnaire 48-items (MTQ48), a widely used measure of mental toughness, we examined data from a sample of 78,947 participants. A series of exploratory structural equation models (ESEM) assessed unidimensional, multidimensional, and bifactor solutions. Overall, results supported a bifactor conceptualization of mental toughness. Bifactor analysis was consistent with the use of a general factor score. In conclusion, the authors argue that mental toughness should be considered as an umbrella term representing a general trait comprised of related constructs that provide a psychological advantage in performance and promote positive mental health. Finally, this article identifies limitations in the existing measurement of mental toughness and proposes necessary directions in future research.